Implementation of sustainable development goal 6 in Ukraine: challenges and obstacles (as example of river Ros’) - Berezovyi, Vlas; Kharchenko, Viacheslav (My University, 2024)
Goal 6 of the sustainable development is “Clean water and sanitation” (“Ensure availability and sustainable management of water and sanitation for all”). The paper considers challenges and obstacles on the way to achieving sustainable use of water resources of the Ros’ River.

Ціль 6 сталого розвитку – «Чиста вода та санітарія» («Забезпечити доступність та стале управління водою та санітарією для всіх»). У цій праці розглядаються виклики та перешкоди на шляху досягнення сталого використання водних ресурсів р. Рось.
Keywords: Ros’ river; sewage treatment facilities; goal 6 of the sustainable development; water resources; річка Рось; очисні споруди; ціль 6 сталого розвитку; водні ресурси; кафедра екології та екоменеджменту